The study of localising mobile game “Fantasy Westward Journey” to Singapore - Chen, Xun (Nanyang Technological University, 2022)
Mobile game localisation is a new domain within translation studies and game localisation studies. Game localisation is becoming an emerging industry within the global entertainment industry. Research in this area contributes to the understanding of mobile game localisation and offers the possibility to explore new directions for this industry. As the number of game developers in China continues to grow, a large number of mobile games are being developed that are attracting players from all over the world. These mobile games are either less localised into English or only intended for specific customers in specific geographic locations. Notably, relatively few studies in this area have been conducted on game localisation from the Chinese market to the Southeast Asian market. Due to the similarities in culture, religion and language between China and Singapore, this study aims to explore the possibility of Chinese game localisation using three translation strategies and determine the acceptability of the Chinese mobile game ‘Fantasy Westward Journey’ (梦幻西游) for people in Singapore. This study used a questionnaire to collect preferences from participants and analyse them. The results indicate that people in Singapore prefer the domestication approach first, followed by either the free translation or literal translation approaches. Thus, it is possible to localise this mobile game for Singapore.